When Local Beats Systemic: Durable Control of Metastatic Undifferentiated Uterine Sarcoma and Surveillance Uncovering a Second Primary - Lapeikis, Ignas; Baranauskytė, Vakarė; Jančiauskas, Dainius; Pužauskienė, Lina; Korobeinikova, Erika (Acta medica Lituanica, 2026)
Introduction: Undifferentiated uterine sarcoma (UUS) is a rare, aggressive uterine mesenchymal malignancy with poor prognosis, for which, evidence supporting metastasis-directed treatment strategies is limited. Case presentation: A 59-year-old woman underwent total hysterectomy with bilateral salpingo-oophorectomy (R0) for stage IB UUS in 2016, followed by adjuvant doxorubicin–ifosfamide. Three years later, surveillance CT identified bilateral pulmonary metastases. Video-assisted thoracoscopic resection confirmed metastatic UUS, and stereotactic body radiotherapy (SBRT) was delivered to residual and subsequent lung lesions, achieving sustained local control without systemic therapy. The patient remained progression-free for almost three years. In 2024, follow-up imaging showed no active sarcoma but incidentally detected a left breast lesion; biopsy revealed invasive ductal carcinoma with mucinous features. She underwent breast-conserving surgery with sentinel lymph node biopsy (pT1N0(sn)), followed by adjuvant whole-breast radiotherapy and endocrine therapy with tamoxifen. Outcomes: At 8.5 years from UUS diagnosis and one year after breast cancer treatment, the patient remains alive with no evidence of recurrent or metastatic disease and with excellent performance status (ECOG 0). Conclusions: This case demonstrates prolonged, chemotherapy-free control of metastatic UUS using a metastasis-directed strategy combining surgery and SBRT, and highlights the importance of continued surveillance for secondary primary malignancies. It supports considering an oligometastatic treatment paradigm and multidisciplinary management in selected UUS patients despite the absence of prospective data.